Large conductance voltage- and calcium-dependent K(+) channel, a distinct member of voltage-dependent ion channels with seven N-terminal transmembrane segments (S0-S6), an extracellular N terminus, and an intracellular (S9-S10) C terminus - Meera, Pratap (The National Academy of Sciences of the USA, 1997)
Large conductance voltage- and Ca(2+)-dependent K(+) (MaxiK) channels show sequence similarities to voltage-gated ion channels. They have a homologous S1-S6 region, but are unique at the N and C termini. At the C terminus, MaxiK channels have four additional hydrophobic regions (S7-S10) of unknown topology. At the N terminus, we have recently proposed a new model where MaxiK channels have an additional transmembrane region (S0) that confers β subunit regulation. Using transient expression of epitope tagged MaxiK channels, in vitro translation, functional, and “in vivo” reconstitution assays, we now show that MaxiK channels have seven transmembrane segments (S0-S6) at the N terminus and a S1-S6 region that folds in a similar way as in voltage-gated ion channels. Further, our results indicate that hydrophobic segments S9-S10 in the C terminus are cytoplasmic and unequivocally demonstrate that S0 forms an additional transmembrane segment leading to an exoplasmic N terminus.